The Matrix in Context: Taking Stock of Police Gang Databases in London and Beyond. (April 2020) - Densley, James A.; Pyrooz, David C.
Technology has ushered in a new era of intelligence-led and 'big data' policing, and police gang databases are part of this paradigmatic shift. In recent years, however, gang databases have come under intense public scrutiny. For example, Amnesty International and others argue that London's Gangs Matrix is discriminatory and violates data-protection laws. This article draws on evidence and examples from a wide range of sources – gang legislation, surveys of young people, police gang records and research on gangs – to put the Matrix controversy into broader context, and to adjudicate between common validity and civil liberties critiques of gang databases.